2005
DOI: 10.1111/j.1751-3928.2005.tb00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Mo-related Adakitic Granitoids from Non-island-arc Setting: Jecheon Pluton of South Korea

Abstract: Abstract:The Jecheon granitoids, having an elongated shape of NE-SW 27 km and NW-SE 13 km (190 km 2 ), are composed mostly of magnetite-series hornblende-biotite granodiorite and biotite granite, which intrude into the Neoproterozoic metamorphic and Paleozoic sedimentary rocks of the Ogcheon Belt. The granitoids have Triassic-Jurassic age of 202.7 ± 1.9 Ma with very high 87 Sr/ 86 Sr initial ratio of 0.7140. The granodiorite has 63-69 % SiO 2 , 15.1-17.3 % Al 2 O 3 , <1.6 % MgO, 6-15 ppm Y and Sr/Y ratios of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
8
0
3
Order By: Relevance
“…Recently, other origins of adakite have been proposed, such as partial melting of thick lower continental crust or delaminated lower continental crust (e.g. Atherton & Petford, 1993; Kay & Kay, 1993; Muir et al ., 1995; Defant et al ., 2002; Ishihara, 2005; Ishihara et al ., 2005). Kamei (2002) suggested that adakitic rocks can be produced by an anatexis of metaluminous tonalite to granodiorite.…”
Section: Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, other origins of adakite have been proposed, such as partial melting of thick lower continental crust or delaminated lower continental crust (e.g. Atherton & Petford, 1993; Kay & Kay, 1993; Muir et al ., 1995; Defant et al ., 2002; Ishihara, 2005; Ishihara et al ., 2005). Kamei (2002) suggested that adakitic rocks can be produced by an anatexis of metaluminous tonalite to granodiorite.…”
Section: Considerationsmentioning
confidence: 99%
“…Judging from the Sr/Y vs. Y diagram and the REE patterns, almost all the Daebo granitic rocks plot in the field of adakitic rocks, but almost all belong to the ilmenite series. These characteristics are different from the original adakite of the magnetite series, derived from partial melting of subducted oceanic crust (Ishihara et al ., 2005). On the basis of Sr–Nd isotope analysis, Jwa (2004) concluded that the source material of the Daebo granitic rocks was continental crust.…”
Section: Considerationsmentioning
confidence: 99%
“…As mentioned previously, the studied plutonic rocks are free of magnetite and have hornblende-biotite and / or biotite assemblages, except for the Busetsu Granites of the Okazaki-Inabu zone, which has (garnet-)muscovite-biotite or biotite assemblage. The granitoids are non-adakitic (Sr / Y < 22, Ishihara et al, 2005), but a few high Sr / Y values are observed in the Shinshiro-Shitara zone (e.g., Nos. 4 and 12), and the Okazaki-Busetsu zone (Nos.…”
Section: Variation Diagrams For the Granitoidsmentioning
confidence: 99%
“…In Korea, the largest Jecheon Mo skarn deposit (Kim & Hwang, ) occurs at the southern margin of pink biotite granite of the magnetite series, Jurassic in age, which is adakitic (Ishihara et al ., ). In the Japanese Islands, major Mo‐deposits are vein type in the magnetite‐series granitic terrane, but stockwork‐type deposits hosted in granitic porphyry dike and plug are present in the center of Pb–Zn skarn deposits of Nakatatsu and Kamioka deposit within the Sanin Eocene Mo‐province of the Inner Zone of SW Japan (e.g., Ishihara, ).…”
Section: Discrimination Of Magnetite/ilmenite‐series Granitoidsmentioning
confidence: 97%